PHYSICAL SOIL C CHARACTERISTICS OF WATERLOGGED AND SALINE LANDS OF FIVE DISTRICTS OF HARYANA, INDIA - Raizada, S.; Chadha, N. K.; Hasan, Javed; Maheshwari, U. K. (Journal of Indian Fisheries Association, 2015)
Physical characteristics of waterlogged and saline soils of five districts,namely Rohtak, Faridabad, Gurgaon, Sonipat and Jhajjar, of Haryana werestudied to evaluate the aquaculture potential. The soil samples from 76 siteswere procured and analysed for pH, electrical conductivity, soil particlesand water retention capacity, since the knowledge of these parameters isessential for the preliminary evaluation of a site for aqua-farming. Six soiltypes were identified and clay-loam was observed to be the maximum at 45(59.21%) sites, followed by silty-clay loam at 14 (18.42%), sandy-clay loam atsix (7.89%), silty-loam at four (5.26%), sandy-loam at four (5.26%) and loam atthree (3.94%) sites. The pH of soil indicated moderate to high alkalineconditions ranging between 8.01and 9.00 at 53 (69.73%) sites, 9.01 and 10.00 at17 (22.36%) sites, and low between 7.01 and 8.00 at six (7.89%) sites. Theelectrical conductivity was found to range between